Canada : 2018 Article IV Consultation-Press-Release; Staff Report; and Statement by the Executive Director for Canada. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
The economy has continued to perform well, but trade tensions, uncertainty about the outcome of NAFTA negotiations and the impact of the U.S. Tax Cuts and Jobs Act on Canada's competitiveness are casting a shadow over the outlook.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet